Analisis Penerapan PSAK No. 109 Tentang Akuntansi Zakat Pada Lembaga Amil Zakat, Infak Dan Shadaqah Al-Haromain Kota Kediri - Utama, Yopi Yudha; Janah, Sidanatul (ITB AAS INDONESIA Surakarta, 2024)
Indonesia's increasing development has an impact on increasing the income of citizens. From this increased income, especially in Islamic teachings, it is mandatory or in other words must be paid through zakat. Zakat, Infaq and Sadaqah are what really move individuals, society and this country forward. However, many cannot distribute their zakat to zakat institutions. The factor of distrust towards zakat institutions is considered to be the main factor, therefore zakat institutions should create guidelines for preparing financial reports in accordance with PSAK No. 109 concerning zakat accounting. The aim of this research is to analyze the suitability of implementing PSAK No. 109 with the accounting system at the Amil Zakat, Infak and Shodaqoh institutions in Kediri. This PSAK No. 109 statement focuses on regulating the recognition, measurement, presentation and transactions of zakat and alms. This type of research is a case study at one of the Amil Zakat Al - Haromain institutions in the city of Kediri. The research method used is descriptive analysis using documentary data collection methods and interview methods. The research results show that LAZIS Al - Haromain in Kediri has not made journal reports, cash flow reports, changes in assets under management, and financial records. LAZIS Al-Haromain only reports changes in funds. Thus, LAZIS Al-Haromain has not implemented PSAK No. 109